2017
DOI: 10.1016/j.ypmed.2017.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with maintenance of body mass index in the Jackson Heart Study: A prospective cohort study secondary analysis

Abstract: The purpose of this study was to compare the relationship of diet quality, physical activity, and environmental factors with body mass index (BMI) maintenance in African American adults. We analyzed data from 4041 participants in the Jackson Heart Study, a prospective cohort study based in Jackson, Mississippi. Exposures were baseline American Heart Association diet quality score, American Heart Association physical activity categories, the built environment, the food environment, and neighborhood safety. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
0
10
1
Order By: Relevance
“…A flowchart of the selection process is presented in figure 1. From the 12 757 identified studies, after screening for relevant titles, abstracts and full manuscripts, 66 articles that fitted the eligibility criteria were selected 30–95. Summary characteristics are shown in table 2 and complete characteristics of the studies are shown in online supplementary file 2.…”
Section: Resultsmentioning
confidence: 99%
“…A flowchart of the selection process is presented in figure 1. From the 12 757 identified studies, after screening for relevant titles, abstracts and full manuscripts, 66 articles that fitted the eligibility criteria were selected 30–95. Summary characteristics are shown in table 2 and complete characteristics of the studies are shown in online supplementary file 2.…”
Section: Resultsmentioning
confidence: 99%
“…For the 2018 PAGAC Report, 33 original studies published through June 2017 that examined the relationship between physical activity and weight gain were included as sources of evidence . The additional search conducted through March 2018 resulted in an additional seven original research studies being included in the literature review (45)(46)(47)(48)(49)(50)(51). Thus, 40 original research studies were included, and a summary of the articles included in this review is shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Most (N=29) of the studies showing an association between greater physical activity and attenuated weight gain were prospective cohort studies (12, 13, 15, 16, 18, 20-22, 25-29, 32-34, 36-44, 49-51), with follow-up periods ranging from 1 to 22 years and one study involving 6-year follow-up after a block randomized controlled trial (14). For the studies not showing an effect (N=11), cohort studies had a follow-up period ranging from 1 to 20 years (17,19,23,24,30,31,35,(45)(46)(47)(48), with three of these studies having follow-up periods of 2 or fewer years (19,22,23,31), and one was a secondary analysis of data from a randomized study (24).…”
Section: Overall Association Between Physical Activity and Attenuation Of Weight Gainmentioning
confidence: 99%
“…This held true even after accounting for consumption of fast food and exercise. A prospective study followed African American adults with a baseline BMI ≥ 18.5 kg/m 2 for a period of 5 years [ 26 ]. Important determinants of maintaining one’s weight or losing vs. gaining weight were healthy nutritional habits and not residing in an unsafe neighborhood which is indicative of decreased psychosocial health.…”
Section: Resultsmentioning
confidence: 99%